Potential role of calcium sulfate/β-tricalcium phosphate/graphene oxide nanocomposite for bone graft application_mechanical and biological analyses - Yung-Chang Lu; Ting-Kuo Chang; Tzu-Chiao Lin; Shu-Ting Yeh; Hung-Shih Lin; Qiao-Ping Cheng; Chun-Hsiung Huang; Hsu-Wei Fang; Chang-Hung Huang (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background Bone grafts are extensively used for repairing bone defects and voids in orthopedics and dentistry. Moldable bone grafts offer a promising solution for treating irregular bone defects, which are often difficult to fill with traditional rigid grafts. However, practical applications have been limited by insufficient mechanical strength and rapid degradation. Methods This study developed a ceramic composite bone graft composed of calcium sulfate (CS), β-tricalcium phosphate (β-TCP) with/without graphene oxide (GO) nano-particles. The biomechanical properties, degradation rate, and in-vitro cellular responses were investigated. In addition, the graft was implanted in-vivo in a critical-sized calvarial defect model. Results The results showed that the compressive strength significantly improved by 135% and the degradation rate slowed by 25.5% in comparison to the control model. The addition of GO nanoparticles also improved cell compatibility and promoted osteogenic differentiation in the in-vitro cell culture study and was found to be effective at promoting bone repair in the in-vivo animal model. Conclusions The mixed ceramic composites presented in this study can be considered as a promising alternative for bone graft applications.